Pilonidal Sinus of the Penis - Hugh F. O'Kane; B. Duggan; C. Mulholland; J. Crosbie (The Scientific World Journal)
A pilonidal sinus is a subcutaneous sinus containing hair. It is most commonly found in the natal cleft of hirsute men. Here we describe the unusual finding of a pilonidal sinus arising on the male foreskin.